NETRALISASI MINYAK HATI IKAN CUCUT PISANG (Charcarinus falciformis) MENGGUNAKAN NaOH - Nabila Ukhty; Anhar Rozi (JURNAL PERIKANAN TROPIS, 2016)
The shark has a yield  by-product from its  liver up to 20% of its body weight, 50% of the total fish oil found on the liver. The aimed of this study was to determine heavy metal content, fatty acid profilel, and parameter of oxidation after neutralization. The method of  heavy metal test for silky shark oil stated on the SNI and fatty acid analysis referred to AOAC. Neutralization used NaOH 18°Be temperature (40, 50, 60, 70, and 80°C). The result of oil neutralization with NaOH had heavy metal content meet to IFOS (0.1 ppm), fatty acid of SFA was 19.58% , MUFA was 19.26 %, and PUFA was 41.58 %. The oxidation result of silky shark liver oil neutralization indicated the best treatment at 50°C with peroxide value (PV), p-Anisidine value (p-AV), percentage of free fatty acid (% FFA), acid value (AV), and total oxidation (TOTOX) were 72,49±0,27 mEq/kg, 8,57±0,46 mEq/kg, 0,28±0,00%, 0,56±0,00 mg KOH/kg, 13,57±1,01 mEq/kg respectively.